Emerging research designs in New Zealand doctoral projects - Cameron, Roslyn (Southern Cross University Press, 2012)
Mixed method research is a growing area of methodological choice for many academics and researchers from across a variety of discipline areas. This chapter provides a brief overview of the rise of mixed methods research, its usage in business and management fields, a discussion on the emergence of mixed methods research designs and presents empirical evidence of mixed methods usage in DBA theses at MIT in New Zealand. * This is based in part on a chapter titled, ‘Changing the paradigm- emerging research designs in professional doctorates’, in Miller, P. and Marchant, T. (Editors) 2009, Professional Doctorate Research in Australia: Commentary and Case Studies from Business, Education and Indigenous Studies, Southern Cross University Press, Lismore.